2021
DOI: 10.1097/md.0000000000026877
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between the effects of drug costs and share of family income on drug costs in determining drug price

Abstract: High health care and medication expenditures pose a financial burden on Americans seeking care. It is imperative to determine the role of affordability in influencing access to health care and medications.To investigate the association between financial burden and health care access by comparing the effects of absolute and relative financial burdens, measured by total health care/medication expenditure (Expenditure) and health care/medication expenditure as a share of annual family income (Expenditure Share), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Studies found that families with children and in particular, low-income families are unable to bear the burden of insurance and out-of-pocket healthcare costs, which prove detrimental to their health needs. 30,31 In our assessment, although ethnicity was not a notable contributing factor toward medication adherence, there were significant regional differences observed across the country. Individuals from the South with more than one CVD risk factor were 1.59 times more likely than those from the Northeast to experience CRMN.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Studies found that families with children and in particular, low-income families are unable to bear the burden of insurance and out-of-pocket healthcare costs, which prove detrimental to their health needs. 30,31 In our assessment, although ethnicity was not a notable contributing factor toward medication adherence, there were significant regional differences observed across the country. Individuals from the South with more than one CVD risk factor were 1.59 times more likely than those from the Northeast to experience CRMN.…”
Section: Discussionmentioning
confidence: 65%
“…Studies found that families with children and in particular, low-income families are unable to bear the burden of insurance and out-of-pocket healthcare costs, which prove detrimental to their health needs. 30, 31…”
Section: Discussionmentioning
confidence: 99%
“…The increase in healthcare costs has garnered public attention for over a decade (Dong et al 2021). Most of healthcare costs are expended on medicines.…”
Section: Introductionmentioning
confidence: 99%